Heat treatment effect on the single oscillator parameters and optical band gap of an organic thin film - Yakuphanoğlu, Fahrettin (Elsevier, 2006)
The effect of heat treatment on the optical band gap and refractive index dispersion of 2,9,16,23-tetraneopentoxyphthalocyaninato zinc(II) thin film has been investigated. The absorption edge with increasing annealing temperature was shifted to the lower energy side and fundamental absorption edge is formed by a direct allowed transition. The refractive index and dispersion parameters E-o and E-d of the thin film were determined. The obtained results show that the film is suitable to change refractive index and oscillator parameters by heat treatment. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: thin film; optical band; refractive index dispersion; heat treatment